2013
DOI: 10.1177/1545968313508467
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinguistic Cognitive Impairment in Poststroke Aphasia

Abstract: Standard nonlinguistic cognitive examination is recommended in aphasic stroke patients. Nonlinguistic cognitive impairments are common and associated with poor functional outcome and depression, especially in patients with persisting aphasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 34 publications
3
82
0
Order By: Relevance
“…For example, executive functioning incorporates skills 20 pertaining to shifting, planning and goal-oriented behavior, whereas, attention may be further 21 differentiated into sustained, selective and divided attention (Lezak, Howieson, & Loring, 22 2004;Murray, 2012). The presence of concomitant cognitive impairments in adults with post-23 stroke aphasia has been well documented (El Hachioui et al, 2014), and impairments in the 24 domains of attention (Erickson, Goldinger, & LaPointe, 1996;Glosser & Goodglass, 1990;25 Murray, 2012;Murray, Holland, & Beeson, 1997;Sturm & Willmes, 1991;Villard & Kiran, 26 2015), memory (Beeson, Bayles, Rubens, & Kaszniak, 1993;Mayer & Murray, 2012;assessment significantly correlated with both spontaneous recovery and treatment success. 1…”
Section: Introductionmentioning
confidence: 99%
“…For example, executive functioning incorporates skills 20 pertaining to shifting, planning and goal-oriented behavior, whereas, attention may be further 21 differentiated into sustained, selective and divided attention (Lezak, Howieson, & Loring, 22 2004;Murray, 2012). The presence of concomitant cognitive impairments in adults with post-23 stroke aphasia has been well documented (El Hachioui et al, 2014), and impairments in the 24 domains of attention (Erickson, Goldinger, & LaPointe, 1996;Glosser & Goodglass, 1990;25 Murray, 2012;Murray, Holland, & Beeson, 1997;Sturm & Willmes, 1991;Villard & Kiran, 26 2015), memory (Beeson, Bayles, Rubens, & Kaszniak, 1993;Mayer & Murray, 2012;assessment significantly correlated with both spontaneous recovery and treatment success. 1…”
Section: Introductionmentioning
confidence: 99%
“…77,81,[114][115][116] In contrast, two studies examining predictors in patients with aphasia found that better scores on a composite measure of phonology and non-linguistic cognitive markers predicted better outcomes one year post-stroke. 77,115 Persad and colleagues looked at predictors in two different ICAPs and similarly found that there was no difference between responders and non-responders on the WAB-R AQ on factors of age, time post-onset, and gender, but did find a difference in severity of aphasia. 73 Similar to this thesis, there was a trend towards older participants who were longer time post-onset having less change on the AQ measure.…”
Section: Structure Of Icapsmentioning
confidence: 99%
“…While some of these factors are difficult to measure or have not been routinely measured, some research has shown that they may positively impact recovery. [77][78][79] Other research has found that such characteristics had minimal or mixed effect on recovery from aphasia. 80,81 Evidence is equivocal about the extent to which stroke-related or neurological characteristics such as time post onset, type of aphasia, and location and size of the lesion impact recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of cognitive impairments in adults with aphasia is high. El Hachioui et al (2014) found that out of a sample of 147 adults with aphasia, 88% of individuals' demonstrated impairment in at least one cognitive domain at 3 months post stroke onset and 80% of individuals continued to demonstrate cognitive impairment(s) at 12 months post-stroke. Consequently, the presence of comorbid cognitive impairments in adults with aphasia is likely to influence participation in rehabilitation and negatively affect therapy outcomes.…”
Section: Influence Of Cognitive Ability On Aphasia Treatment Successmentioning
confidence: 99%